Enhancing Girls’ Education through CCA - Madhavi, R.L. (THE PRIMARY TEACHER, 2006)
“The question of the education of children cannot be solved unless efforts are made simultaneously to solve the girls education,” said Gandhji. The adage “If a woman is educated, an entire family is educated,” emphasises the importance of providing a proper education to the girl child. Even though in ancient times there were equal opportunities for women in the field of education, later social climate prevented girls from moving out of home; this affected their education. Subsequent industrialisation world over; changed the role of women to a great extent. Women were required to fulfill responsibilities within and outside the home. So, the emphasis once again turned towards providing proper education to women, especially girls. In the Indian context, after achieving Independence, the women’s education movement gained momentum. The constant efforts made by the government has raised literacy rate among women to 48 per cent.Traditional mindset, conservatism, security reasons, and a lack of awareness of the need to and the importance of educating a girl child, prevents the rural girl child from obtaining an education. This reluctance towards education in rural areas, is impeding efforts being made in the field of female education in Indian society. Concerted efforts to bring in the rural girl child into the formal education system and to retain them in the system up to the required level included many interactive programmes. In the present paper, the authors try to detail various CCA activities like role play, bhavai, mono-act. debate, elocution, etc. to involve girl students in an interactive teaching learning process